Main problems of manufacturing asphalt concrete mixtures in Lithuania/Asfaltbetonio mišinių gamybos svarbiausios problemos Lietuvoje - Čygas, Donatas (Journal of Civil Engineering and Management, 2000)
The article describes the main problems of manufacturing asphalt concrete mixtures at the factories under Ministry of Communication in the Republic of Lithuania. The Lithuanian Road Network is up to 21.122 km of state roads. 1.455 km of them are motorways, 3.415 km – national roads and 16.251 km – regional roads. Half of the state roads in Lithuania are paved with asphalt concrete. 98% of the motorways and 36% of the regional roads have asphalt pavement. Asphalt concrete pavement resistance to corrosion can be increased by improving asphalt concrete mixture production technology: ie by updating technological equipment, changing technological conditions and developing new methods of asphalt concrete mixture production. Therefore, the updating of asphalt concrete mixture production technologies is a very important factor for improving road operating properties and ensuring proper duration of asphalt concrete pavements. Here is the essence of the new separate successive technology: crushed stone and sand are mixed with bitumen in the main asphalt concrete mixer, the amount of bitumen being calculated according to the bitumen absorption in the materials. Then the asphalt cement material produced in a separate high-speed mixer is passed, and the whole mixture is remixed in the main mixer and supplied to the customer. Both separate consequent technologies differ from each other in the order of supplying asphalt cement material into the main mixing unit. Separate successive technology was theoretically grounded by the correlation between the technological thickness of bituminous film and the chemical-mineralogical composition and size of constituents, by the correlation between the particle size and their capability to compose aggregates, by the emergence of the oriented binding material coating on the technological bituminous film encoating mineral particles. Special attention is given to the manufacturing of asphalt cement material in a separate high-speed mixer (3 Table). It was theoretically grounded that mineral filler passing through the intensive shift zone between the paddle ends of the high-speed mixer and the walls of mixing chamber disintegrate and new active surfaces become visible. The molecular structure changes and free radicals appear. This intensive mixing guarantees high bitumen adsorption on the surface of mineral filler, which increases asphalt concrete resistance to corrosion and its durability, improves ecological environment in the asphalt concrete plant. In order to confirm the reliability of research results and explain correlative and regressive regularity, statistical data were processed applying statistical data processing programming system “STATGRAPHICS”. The linear regressive analysis for determining close relations of separate asphalt concrete quality indicators with speed gradient of asphalt cement material shift in a high-speed mixer was performed. Therefore, the possibility to change shift speed gradient from 3000 to 5000 1/s is provided in terms of reference for manufacturing asphalt concrete mixing plant. Correlation between separate asphalt concrete quality indicators and asphalt cement material shift speed gradient as well as bitumen amount in the asphalt cement material was determined by multi-dimensional regressive analysis of experimental data. The calculated correlation factor squared (R2) and F criteria indicate the adequacy and reliability of the multidimensional regression model.Article in Lithuanian.First Published Online: 26 Jul 2012